THE EFFECT OF AUDIO-LINGUAL REPETITION DRILLING ON EFL LEARNERS' SPEAKING AND LISTENING COMPREHENSION - Chelsea Chahya Ningrat; Lili Sururi Asipi; Utami Rosalina (NextGen Education Review Journal, 2025)
This study investigates the effectiveness of Audio-Lingual Repetition Drills (ALRD) in improving speaking and listening skills of EFL learners. A quantitative design was conducted with 60 vocational high school students in West Java, Indonesia, using speaking and listening tests along with questionnaires. Data were analyzed through IBM SPSS Statistics 26. The speaking test, assessed by an analytic rubric, recorded an average score of 79.53, while the listening test, consisting of 20 multiple-choice items, showed an average of 77.85. Both results fall into the “good” category, with improvements especially in fluency, pronunciation, and comprehension. A strong positive correlation (r = 0.691, p < 0.05) was found between speaking and listening, showing that improvement in one skill supported gains in the other. Students also indicated that repetition drills increased their confidence and focus. This study highlights the practical application of ALRD in English teaching, particularly in vocational schools, and provides new evidence of its integrated effect on both speaking and listening skills